Fighting The Cold: The Need for Standing Cold Weather Combat Capabilities - Bechtol, John G. (2002)
The United States should create and maintain the capability of rapidly deploying forces into cold regions to conduct sustained combat operations. It is recommended that these forces be comprised of an Army division, a Marine Expeditionary Unit, an Air Expeditionary Force, and a Carrier Battle Group. The vast majority of United States military units have a permanent mission of being able to deploy anywhere in the world to fight and win the nation's wars. History has shown that unprepared military forces deployed to cold weather combat may suffer severe losses from the climate. An example of poorly prepared forces suffering unnecessary casualties due to the weather is the Aleutian Campaign of World War II. The preponderance of current cold weather training conducted among the services is focused on survival, and not on operations. Therefore, a Joint Arctic Combat Training Center should be created to train and evaluate the readiness of arctic-designated units. The Department of Defense and the respective services should correlate home-station climate and anticipated contingency operations. Existing equipment may be better modified for use in the cold, and antiquated equipment should be eliminated or replaced. Faced with combat in continuous below-zero temperatures, the operational commander must make his choices carefully using the operational factors and functions. The confidence that he can introduce acclimatized forces into a cold weather theater with no further training gives the operational commander more options, and a better chance for victory. The original document contains color images.